Aboriginal peoples of Chukotka - Abryutina, Larisa (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractBefore the Aboriginal peoples of Chukotka were introduced to European culture, they lived a traditional way of life which defined their material and spiritual culture. During the integration into the Russian State, all spheres of their life went through various transformations. This article presents an overiew of the history of Aboriginal peoples of Chukotka (Yupiget, Chukchi, Evens, Koryaks, Chuvans, Yukagirs and Kereks).